In dulci iubilo - Jørgensen, Ninna (Dansk Teologisk Tidsskrift, 2012)
Luther’s Christmas sermons 1525-1530 constitute an identifi - able entity. In his yearly efforts to present the “old” announcement to his congregation, he uses a set structure. He retells Luke’s gloomy birth narrative from a historical point of view and introduces, in marked contrast, the angelic revelation of the divine secret behind this humble appearance. The pronouncement of a saviour born “to you/us/ me” is the fi rst and fundamental sermon in the new dispensation. Joy and praise remain its response. Luther’s integral use of liturgical celebration is viewed in relation to the preaching by esp. Bernard of Clairvaux, whom he admired greatly. It is furthermore argued that his conscious affi liation to traditional elements of worship is not only a product of his confrontation with the “spiritualists”, but can also be seen as an acknowledgement of the sermon’s function in service and the need of talking and catechizing to the senses.